2011
DOI: 10.1016/j.jcrs.2011.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual performance with an aspheric intraocular lens and a spherical intraocular lens

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(44 reference statements)
1
11
0
2
Order By: Relevance
“…They reported a difference of approximately three letters in favor of the Tecnis Z9000 IOL implants. On the other hand, Thiagarajan et al14 found a statistically significant difference in CDVA but not clinically important (relative difference 1.5%), between Akreos Adapt Advanced Optics (AO) (Bausch and Lomb, Inc, Rochester, NY) aspheric intraocular lens (IOL) and the Sensar AR40e spherical acrylic IOL, in favor of the spherical IOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a difference of approximately three letters in favor of the Tecnis Z9000 IOL implants. On the other hand, Thiagarajan et al14 found a statistically significant difference in CDVA but not clinically important (relative difference 1.5%), between Akreos Adapt Advanced Optics (AO) (Bausch and Lomb, Inc, Rochester, NY) aspheric intraocular lens (IOL) and the Sensar AR40e spherical acrylic IOL, in favor of the spherical IOL.…”
Section: Discussionmentioning
confidence: 99%
“…Munoz et al2 found that both the PCS and MCS were similar in patients that received implants of Tecnis Z9000, Sensar AR40e, or Stabibag IOLs. Also, Thiagarajan et al14 found no statistically significant differences in contrast sensitivity between Akreos Adapt Advanced Optics aspheric intraocular lens (IOL) and the Sensar AR40e spherical acrylic IOL.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] who reported comparable visual performance and contrast sensitivity between Tecnis Z9003, AcrySof IQ SN60WF and Akreos Adapt AO after phacoemulsification. [ 3 ] Similar outcomes have been reported by Thiagarajan et al .,[ 4 ] Rodríguez-Galietero et al .,[ 5 ] Kurz et al .,[ 6 ] Pandita et al .,[ 7 ] Caporossi et al .,[ 8 ] Mester and Kaymak,[ 9 ] and Santhiago et al . in past.…”
Section: Discussionmentioning
confidence: 99%
“…Neben den verbesserten operativen Techniken haben die Patienten am meisten von den Vorteilen der Weiterentwicklung des Linsendesigns profitiert. Die Einführung von neuen Linsenmaterialien sowie der Wechsel von einem 3-stückigen zu einem 1-stückigen Haptikdesign ermöglichen nicht nur, die Intraokularlinsen durch eine Mikroinzision zu implantieren [1,2], sondern auch deren optische Qualität zu verbessern [3][4][5][6][7][8]. Außerdem kann derzeit die postoperative sphärische Aberration der Hornhaut durch die Implantation einer asphärischen Intraokularlinse (IOL) im Rahmen der Kataraktoperation optimiert werden [8][9][10][11][12].…”
unclassified
“…Thiagarajan et al[6] hatten die Sehleistung nach Kataraktextraktion bei Implantation einer asphärischen mit einer sphärischen IOL verglichen und dabei keinen signifikanten Unterschied in der Entwicklung von Dysphotopsien oder in der Patientenzufriedenheit gefunden. Es sollte jedoch berücksichtigt werden, dass in dieser Studie ein anderes asphärisches IOL-Modell durch einen anderen subjektiven Fragebogen evaluiert wurde.…”
unclassified